The use of gamma rays in studying the homogeneity of the alloy (AL-Co-Ni) reinforced with chromium oxide - raad rasool; Laith Rabih; Ali Huseen (College of Education for Pure Sciences, 2021)
This research deals with the preparation number of composite materials by casting the base alloy (Al-Co-Ni) by adding chromium oxide (Cr2O3) as reinforcement material, by weight ratios of (5, 10, 15 wt%) for the base alloy, with heat treatment of the prepared alloys. The basic alloys and composite materials were prepared by using solution casting method and manual mixing method to disperse reinforcement grains in the base alloy floor and with pressure of 5 ton in purpose of forming. The materials were melted and poured into molds and suddenly cooled in cold water, after the molten samples were frozen. The attenuation factor of gamma rays was founded the prepared alloys and their homogeneity was examined by shining a narrow beam of single energy gamma rays emitted from the radiating source (137Cs) with different energies (511, 662, 1173, 1284, 1333) keV respectively, gamma ray system (UCS-20) was being used which bounded to NaI(Tl) scintillation detector. The homogeneity of base alloy and composite material was determined by studying the contrast of gamma ray intensity, the linear attenuation coefficient at seven different locations at any samples and the percentage standard deviation. The results showed that the highest value of the linear attenuation coefficient was 0.252 mm-1 for sample [5%Cr2O3+Al+Co+Ni] with the energy (511 keV) and that the lowest value for the ratio of linear attenuation coefficient was 0.062 mm-1 at the energy of sample [15%Cr2O3+Al+Co+Ni] with the energy (1333 keV) indicating that the homogeneity of the sample [15%Cr2O3+Al+Co+Ni] at energy (1333 KeV).